HALP and PNI Score as Predictors of Nutritional Status in the Incidence of Incisional Hernia after Laparotomy in Colorectal Cancer Patients: A Case-Control Study - Nurasti, Wawan Suci; Handaya, Adeodatus Yuda; Barmawi, Agus; Anwar, Sumadi Lukman (Indonesian Journal of Cancer, 2024)
Background: Colorectal cancer ranks as the third most common cancer in the world. If patients can still be resected, surgical therapy is carried out. An incisional hernia is one of the complications after laparotomy surgery. Nutritional status can influence the incidence of incisional hernias after laparotomy. Colorectal cancer patients must have their nutritional status assessed using a simple scoring. This research aims to evaluate Hemoglobin, Albumin, Lymphocyte, Platelet (HALP) and Prognostic Nutritional Index (PNI) scores as a predictor of incisional hernia after laparotomy surgery in colorectal cancer patients at Dr. Sardjito General Hospital, Yogyakarta. Methods: This study uses a case-control study design which consisted of two groups, a case group of colorectal cancer patients with incisional hernias after laparotomy surgery and a control group of colorectal cancer patients without incisional hernias. The independent variable was nutritional status which was assessed by HALP and PNI score, and the dependent variable was incisional hernia. This research by taking data from laboratory patients at Dr. Sardjito General Hospital, Yogyakarta. For multivariate analysis, a logistic regression test was used with a significance value of p 0.05. Results: There is a relationship between the stage of cancer and the comorbid diabetes mellitus with the incidence of incisional hernias after laparotomy, this can be seen in the results of the chi-square test. Advanced stage has an OR of 13 (P=.001; OR=13; 95% CI 3.551-47.597), while comorbid diabetes mellitus has an OR of 6.571 (P=.002; OR=6.571; 95% CI 2.109-20.479). However, there is no correlation between the HALP and PNI score with the incidence of incisional hernia after laparotomy. The multivariate analysis results in HALP score have a significant correlation between the nutritional status and the incidence of incisional hernia with OR=17.981 (p= 0.037 OR=17; 95% CI 1.198-269.803). Conclusions: The HALP score can be used as a screening predictor in the incidence of incisional hernia after laparotomy for colorectal cancer patients.